Measuring the effectiveness and efficiency of the recruitment and selection process of DBH Finance Corp Ltd. - Hossain, A.K.M Rabbul (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.